The power of painting - McKenna, Kathleen (Cardiovascular Diagnosis and Therapy, 2013)
My goal as an artist is to utilize all that is abstract in the painting process to create a presence. I want my work to deliver something that is visceral. When I look at my painting (Figures 1-4), whether it is a commissioned portrait, a figure from imagination or a flower from my garden, I want to feel the presence of my subject.